Siedlungsprozesse und territoriale Aneignung im zentralen Hunza-Tal.: Kulturgeographische Anmerkungen zur Karte Hunza-Karakorum 1 : 100000 - Kreutzmann, Hermann (ERDKUNDE, 1996)
Although some of the scientific results of the 1950s expeditions to the Northwest-Karakoram have been utilized for different research purposes only now the topographic map of the area under study has been published. As a commentary from a cultural-geographical perspective some remarks are presented which emphasize on the historical development of present-day villages. The evolution of original settlements and subsequent off-branchings are presented. With knowledge about lineage group composition and origin of water works as well as with evidence from colonial reports and travelogues the settlement history of the former semiautonomous principalities of Hunza and Nager is reconstructed. Investigations into the population structure are based on linguistic and denominational criteria and help to understand the separate developments taking part in Hunza and Nager. Three settlement regions could be distinguished in altitudinal sequence along the Hunza River. Basically they correlate with the habitats of three dominant linguistic groups. Settlement history underlines that the Hunza River has acted as a border between Hunza and Nager and has furnished a prominent regional boundary without permitting much transgression of intra-montane migrants. Nevertheless settlement processes feature many similarities in both valley societies. Prior to colonial penetration villages were founded as fortified habitations, a phenomenon which has vanished afterwards. After 1891 new settlements are located within the village lands as small and comparatively open hamlets thus reducing the distance between homestead and agricultural fields. Internal meliorisation continues as a result of the further establishment of irrigated oases, but at the same time out-migration down the valley commences. Since the first half of the 20th century enclaves of Hunza and Nager migrants are situated in the vicinity of and within Gilgit Town, the administrative centre of the Northern Areas of Pakistan. After independence only a few new villages have been founded, but existing villages have expanded their cultivated areas and their irrigation networks. The agricultural resource potential of villages as it is composed of terraces for grain crops, orchards with fruit trees and irrigated meadows augmented by livestock-keeping and the seasonal utilization of high pastures has undergone a significant transformation in re cent years. The ease of Karimabad in the 1990s is discussed in greater detail and shows how external incomes derived from migrant labour and tourism affect the local economy and especially the significance of mountain agriculture.